(untitled) (Al-Nahrain Journal for Engineering Sciences, 2022)
This research studies the physical and mechanical properties of mortar composed of PVC plastic waste particles used as fine aggregate replacement material. PVC particles in quantities of 5%, 10%, 15%, 20%, 25%, and 30% by volume were used for sand fraction substitution. This quantity of PVC was used to formulate seven mixes with a cement content of 525 kg/m3 and a water-to-cement ratio (w/c) of 0.45. At 7 and 28 days, the compressive and splitting tensile strengths of the mortar's mechanical characteristics were evaluated. Additionally, the physical characteristics of density and absorption were investigated. The findings demonstrated that the mechanical properties and density of mortar containing PVC powder were minimized.